2004
DOI: 10.1007/bf03393185
|View full text |Cite
|
Sign up to set email alerts
|

Studies using single-subject designs in sport psychology: 30 years of research

Abstract: A prominent feature of behavior-analytic research has been the use of single-subject designs. We examined sport psychology journals and behavioral journals published during the past 30 years, and located 40 studies using single-subject designs to assess interventions for enhancing the performance of athletes and coaches. In this paper, we summarize that body of research, discuss its strengths and limitations, and identify areas for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 64 publications
3
49
0
4
Order By: Relevance
“…BUnmotivated students^have been reported by dance teachers as one of the most stressful aspects of teaching (Robson, Book, & Wilmerding, 2002). The subject of motivating athletes during practice is a significant area of research in sports psychology (Martin et al, 2004). For competitive sports environments, interventions such as public posting have been proven to enhance motivation and therefore improve performance in sports (e.g., Brobst & Ward, 2002;Ward & Carnes, 2002).…”
mentioning
confidence: 99%
“…BUnmotivated students^have been reported by dance teachers as one of the most stressful aspects of teaching (Robson, Book, & Wilmerding, 2002). The subject of motivating athletes during practice is a significant area of research in sports psychology (Martin et al, 2004). For competitive sports environments, interventions such as public posting have been proven to enhance motivation and therefore improve performance in sports (e.g., Brobst & Ward, 2002;Ward & Carnes, 2002).…”
mentioning
confidence: 99%
“…2) Futuras pesquisas poderiam utilizar delineamentos de caso único (Martin, Thompson & Regher, 2004), avaliar os efeitos de procedimentos específicos, separadamente, e não em pacotes de intervenção como feito neste estudo, e investigar os efeitos das intervenções com treinadores sobre os comportamentos dos atletas -a partir de observações diretas de seu comportamento, e não somente a partir de medidas indiretas.…”
Section: Considerações Finaisunclassified
“…For example, across disciplines within behavioral science, such as education, school psychology, and vocational rehabilitation, the multiple baseline has been the most frequently applied single-case research design, followed by the A-B-A-B design, while the A-B design has been the most prevalent practitioner (nonexperimental) design (Alberto & Troutman, 2012). Within the discipline of sport psychology, spanning 30 years and 42 studies, Martin, Thompson, and Regehr's (2004) review of single-case research designs used to evaluate interventions that aimed to improve performance of athletes and coaches indicated that 31 of the 42 (74%) studies utilized a multiple baseline design; 8 of 42 (19%) utilized an A-B-A-B design; combined designs were used less frequently and the changing criterion design was used in two of the 42 (5%) studies. Moreover, Barker, Mellalieu, McCarthy, Jones, and Moran's (2013/this issue) follow-up review of literature from 1997-2012 indicates 66 published studies using single-case designs.…”
Section: Introductionmentioning
confidence: 99%